Clinical Variability of Primary Congenital Glaucoma in a Spanish Family With Cyp1b1 Gene Mutations. Issue 8 (October 2015) - Morales-Fernandez, Laura; Martinez-de-la-Casa, Jose M.; Garcia-Bella, Javier; Mendez, Carmen; Saenz-Frances, Federico; Garcia, Maite; Escribano, Julio; Garcia-Feijoo, Julian
Abstract : Background: Primary congenital glaucoma (PCG) is a rare disease. In around a third of Spanish patients, the disease is attributed to mutations in the CYP1B1 gene inherited in an autosomal recessive manner. Such mutations are the main known genetic cause of PCG. Case Report: We describe the case of a family with 3 of 7 siblings diagnosed with PCG. In a genetic study of the CYP1B1 gene, 2 null mutations were identified in the affected siblings (R355fsX69/T404fsX38). Two of the 4 healthy siblings were heterozygous for mutation R355fsX69 and the remaining 2 had no mutations. The healthy parents were found to be heterozygous for mutations T404fsX38 (mother) and R355fsX69 (father). High variation in the expression of PCG was observed, especially in terms of disease onset and severity: Patient 1 in the eldest affected sibling, PCG was diagnosed at 8 years of age and is presently stable after 60 months of medical treatment; patient 2 the second affected child underwent surgery at 7 days of age. Today, at 104 months, she has undergone 2 operations on the right eye and 3 on the left eye; patient 3 the youngest sibling, the disease also manifested at birth and the boy underwent surgery at 4 days. Currently he is 84 months old, he has required 7 operations for glaucoma, 3 in the right eye and 4 in the left. Conclusions: This clinical case reveals the etiological relationship between CYP1B1 mutations and PCG. In addition, it indicates a highly variable clinical picture associated with a single disease genotype mainly affecting disease onset and progression.